β-catenin ISGylation promotes lipid deposition and apoptosis in ethanol-stimulated liver injury models - Qi Ding; Guodong Zhang; Yang Wang; Lei Xu; Meifei Wu; Yiwen Zhou; Tao Xu; Xiaoming Meng; Cheng Huang; Lei Zhang (Taylor & Francis Group, 2022)
Background The restoration of the Wnt/β-catenin pathway to alleviate alcoholic fatty liver disease (AFLD) progression is under study as a new strategy for alcoholic liver disease (ALD) treatment. Recent studies have indicated that interferon-stimulated gene 15 (ISG15) can covalently bind to β-catenin by HECT E3 ubiquitin ligase 5 (HERC5), leading to ISG degradation and downregulation of β-catenin levels. However, the relationship between β-catenin and the ISG15 system in AFLD remains unclear.Methods Here, we explored the roles of the ISG15 system in β-catenin activation and in the pathogenesis of alcohol-induced liver injury and steatosis.Results In this study, HERC5 silencing upregulated β-catenin protein expression and inhibited lipid metabolism disorders and cell apoptosis. Reduced β-catenin protein expression, increased lipid metabolism disorders, and cell apoptosis were detected in cells induced with HERC5 overexpression, which was reversible with the reactive oxygen species (ROS) inhibitor. All the above results were statistically analyzed. Thus, these observations demonstrate that β-catenin ISGylation is a prominent regulator of ALD pathology, which works by regulating ROS to induce lipid metabolism disorders and cell apoptosis.Conclusion Our findings provided the mechanism involved in the β-catenin ISGylation, allowing for future studies on the prevention or amelioration of liver injury in ALD.